Tissue transglutaminase is involved in mechanical load–induced osteogenic differentiation of human ligamentum flavum cells. (3rd July 2016) - Chao, Yuan-Hung; Huang, Shih-Yung; Yang, Ruei-Cheng; Sun, Jui-Sheng
ABSTRACT: Mechanical load–induced osteogenic differentiation might be the key cellular event in the calcification and ossification of ligamentum flavum. The aim of this study was to investigate the influence of tissue transglutaminase (TGM2) on mechanical load–induced osteogenesis of ligamentum flavum cells. Human ligamentum flavum cells were obtained from 12 patients undergoing lumbar spine surgery. Osteogenic phenotypes of ligamentum flavum cells, such as alkaline phosphatase (ALP), Alizarin red-S stain, and gene expression of osteogenic makers were evaluated following the administration of mechanical load and BMP-2 treatment. The expression of TGM2 was evaluated by real-time PCR, Western blotting, and enzyme-linked immunosorbent assay (ELISA) analysis. Our results showed that mechanical load in combination with BMP-2 enhanced calcium deposition and ALP activity. Mechanical load significantly increased ALP and OC gene expression on day 3, whereas BMP-2 significantly increased ALP, OPN, and Runx2 on day 7. Mechanical load significantly induced TGM2 gene expression and enzyme activity in human ligamentum flavum cells. Exogenous TGM2 increased ALP and OC gene expression; while, inhibited TG activity significantly attenuated mechanical load–induced and TGM2-induced ALP activity. In summary, mechanical load–induced TGM2 expression and enzyme activity is involved in the progression of the calcification of ligamentum flavum.